Clinical and biomarker profiling of prodromal Alzheimer's disease in workpackage 5 of the Innovative Medicines Initiative PharmaCog project: a 'European ADNI study'. (4th March 2016) - Galluzzi, S.; Marizzoni, M.; Babiloni, C.; Albani, D.; Antelmi, L.; Bagnoli, C.; Bartres‐Faz, D.; Cordone, S.; Didic, M.; Farotti, L.; Fiedler, U.; Forloni, G.; et al.
Abstract: Background: In the field of Alzheimer's disease (AD), the validation of biomarkers for early AD diagnosis and for use as a surrogate outcome in AD clinical trials is of considerable research interest. Objective: To characterize the clinical profile and genetic, neuroimaging and neurophysiological biomarkers of prodromal AD in amnestic mild cognitive impairment (aMCI) patients enrolled in the IMI WP5 PharmaCog (also referred to as the European ADNI study). Methods: A total of 147 aMCI patients were enrolled in 13 European memory clinics. Patients underwent clinical and neuropsychological evaluation, magnetic resonance imaging (MRI), electroencephalography (EEG) and lumbar puncture to assess the levels of amyloid β peptide 1–42 (Aβ42), tau and p‐tau, and blood samples were collected. Genetic ( APOE ), neuroimaging (3T morphometry and diffusion MRI) and EEG (with resting‐state and auditory oddball event‐related potential (AO‐ERP) paradigm) biomarkers were evaluated. Results: Prodromal AD was found in 55 aMCI patients defined by low Aβ42 in the cerebrospinal fluid (Aβ positive). Compared to the aMCI group with high Aβ42 levels (Aβ negative), Aβ positive patients showed poorer visual ( P = 0.001), spatial recognition ( P < 0.0005) and working ( P = 0.024) memory, as well as a higher frequency of APOE 4 ( P < 0.0005), lower hippocampal volume ( P = 0.04), reduced thickness of the parietal cortex ( P < 0.009) and structural connectivity of the corpus callosum ( P < 0.05), higher amplitude of delta rhythms at rest ( P = 0.03) and lower amplitude of posterior cingulate sources of AO‐ERP ( P = 0.03). Conclusion: These results suggest that, in aMCI patients, prodromal AD is characterized by a distinctive cognitive profile and genetic, neuroimaging and neurophysiological biomarkers. Longitudinal assessment will help to identify the role of these biomarkers in AD progression.